Pengaruh Dana Desa dan Belanja Modal (Infrastruktur) Terhadap Tingkat Kemiskinan Di Kabupaten Bekasi Periode 2019-2024: The Effect of Village Funds and Capital Expenditure (Infrastructure) on Poverty Levels in Bekasi Regency, 2019–2024 - Aqilah Virgi Maryam; Nurul Ayu Aprilia (AMANAH: Jurnal Manajemen Keuangan Sektor Publik, 2026)
This study aims to analyze the effect of Village Funds and capital expenditure on infrastructure on poverty levels in Bekasi Regency during the period 2019–2024. Poverty remains a major development challenge, particularly in regions with industrial economic characteristics such as Bekasi Regency. This research employs a quantitative approach with a causal explanatory design using annual time series secondary data. The data were obtained from official government institutions, including the Central Bureau of Statistics and regional budget realization reports. The analytical method used is multiple linear regression to examine both partial and simultaneous effects of Village Funds and capital expenditure on poverty levels. The results show that, partially, Village Funds do not have a significant effect on poverty levels. Likewise, capital expenditure on infrastructure also does not significantly affect poverty reduction. Simultaneously, Village Funds and capital expenditure are not proven to have a significant impact on poverty levels in Bekasi Regency during the study period. These findings indicate that the allocation of fiscal resources does not automatically lead to poverty reduction in the short term. The effectiveness of poverty alleviation policies depends not only on the amount of budget allocated but also on the quality of planning, targeting accuracy, and implementation. Therefore, it is recommended that local governments improve the effectiveness of Village Fund management and infrastructure spending to achieve more inclusive and sustainable poverty reduction outcomes.